The hippocampus is crucial for forming non-hippocampal long-term memory during sleep. (6th December 2018) - Sawangjit, Anuck; Oyanedel, Carlos; Niethard, Niels; Salazar, Carolina; Born, Jan; Inostroza, Marion
Abstract There is a long-standing division in memory research between hippocampus-dependent memory and non-hippocampus-dependent memory, as only the latter can be acquired and retrieved in the absence of normal hippocampal function1, 2 . Consolidation of hippocampus-dependent memory, in particular, is strongly supported by sleep3–5 . Here we show that the formation of long-term representations in a rat model of non-hippocampus-dependent memory depends not only on sleep but also on activation of a hippocampus-dependent mechanism during sleep. Rats encoded non-hippocampus-dependent (novel-object recognition6–8 ) and hippocampus-dependent (object–place recognition) memories before a two-hour period of sleep or wakefulness. Memory was tested either immediately thereafter or remotely (after one or three weeks). Whereas object–place recognition memory was stronger for rats that had slept after encoding (rather than being awake) at both immediate and remote testing, novel-object recognition memory profited from sleep only three weeks after encoding, at which point it was preserved in rats that had slept after encoding but not in those that had been awake. Notably, inactivation of the hippocampus during post-encoding sleep by intrahippocampal injection of muscimol abolished the sleep-induced enhancement of remote novel-object recognition memory. By contrast, muscimol injection before remote retrieval or memory encoding had no effect on test performance, confirming that the encoding and retrieval of novel-object recognition memory are hippocampus-independent. Remote novel-object recognition memory was associated with spindle activity during post-encoding slow-wave sleep, consistent with the view that neuronal memory replay during slow-wave sleep contributes to long-term memory formation. Our results indicate that the hippocampus has an important role in long-term consolidation during sleep even for memories that have previously been considered hippocampus-independent. Hippocampal activity during a period of sleep after memory encoding is crucial for forming long-term memories in rats, even for types of memory considered not to be hippocampus-dependent.